"Al-Khabith"—The malignant cunning disease: Sociocultural complexity and social representations of cancer in the occupied Palestinian territory. (March 2019) - Albarghouthi, Samar Issa; Klempe, Sven Hroar
This qualitative research aims to understand the sociocultural complexity and social representations of cancer in the occupied Palestinian territory. The researcher conducted 16 in-depth semi-structured individual interviews with Palestinians from the occupied Palestinian territory, using thematic analysis as a methodology and social representation theory as the theatrical framework. The findings revealed three main themes. The first theme is social representations of cancer and cancer treatments divided into four subthemes: (1.1) manifestations of dilemmatic indeterminacy and vagueness. The second subtheme (1.2) refers to social representations of cancer in close proximity with death. The third subtheme (1.3) is constituted by metaphorical social representations of cancer, and the fourth (1.4) refers to social re-presentations of cancer. The second theme is the paradoxical social representations of cancer patients as divided into three subthemes: (2.1) pity-based societal responses, (2.2) manifestations of stigma, and (2.3) cancer rumors, a form of collective sense-making. The third theme, religious discourses and social representations of cancer, is divided into three subthemes: (3.1) cancer as predestined by the will of God, (3.2) cancer as a punishment or a trial, and (3.3) a spiritual journey of healing. The implications of this research suggest that social representations research can take a lead in promoting social and health change. The biomedical paradigm alone is failing in Palestine to encounter the sociocultural complexity connected to representations of cancer and its impact on future-health behaviors. Thus, stakeholders and policy-makers in Palestine need to build a mutual interaction between scientific encounters and lay thinking encounters. This requires building community-based health interventions and a sustainable health promotion programs to ensure higher penetration to the social outreach (families, hospital setting, clinics, and schools). To combat ill-health beliefs, stakeholders can benefit from utilization of community participation through creating space for dialogue and debate about cancer and its representations, which accordingly moving towards social and health change.